Antibacterial activity of Malaysian produced stingless-bee honey on wound pathogens - Nursyamimi Farhana Mat-Kamir (2021)
The antibacterial activity of Malaysian stingless bee honey was tested on six common wound pathogens using agar well diffusion. All pathogens showed varying degrees of susceptibility to undiluted and diluted honeys produced by Geniotrigona thoracica of multifloral source (GTM) and Melastoma malabathricum L (Senduduk). Multifloral honey from Heterotrigona itama (HTM) failed to inhibit the growth of all pathogens, except for methicillin-resistant Staphylococcus aureus (MRSA)which has demonstrated moderate susceptibility to undiluted honey. It was found that the antibacterial activity of GTM and Senduduk honey were concentration dependent. The minimum inhibitory concentration (MIC) assay showed that a lower value (3.13% v/v) was observed with GTM honey for all pathogens and Senduduk honey for Streptococcus pyogenes, MRSA, Staphylococcus aureu sand Pseudomonas aeruginosa, respectively. Interestingly, HTM honey showed MIC between 6.25 to 12.5% (v/v) inmicrodilution method. The minimum bactericidal concentration (MBC) of GTM honey ranged between 6.25 to 12.5% (v/v), where as Senduduk and HTM honeys showed MBC of 25% (v/v). The lower MIC and MBC values exhibited by GTM honey indicates potent antibacterial activity as seen in this honey. This study revealed that the Malaysian stingless bee honeys have promising antibacterial activity against wound pathogens, and this type of honey could be used as an alternative in treating infected wounds.